OBSERVATIONAL STUDY REGARDING THE MOTRICAL DEVELOPMENT LEVEL OF 9-10 YEAR OLD MIRON COSTIN SUCEAVA SECONDARY SCHOOL STUDENTS - Petrariu Ileana (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
Physical development is the result of direct action on the body through simple and compound physical exercises that can be precisely located at the segments, joints, muscle groups level, stimulating and refining its morphological and functional indices. In childhood, organized exercises practicing leads both fair and harmonious development of the body, but also the qualitative development and strengthening motor skills